Mujeres dramaturgas obreras a principios del siglo xx en Chile y la estrategia de la escritura solapada (2016)
This article is from the exploratory study and presentation of a scriptural creation which in turn is an “writing”, which was instituted in a particular dramaturgical word, which in turn defined a historical process, specifically we talk about proletarian women’s contribution in the creation, representation and reception of Chilean anarchist drama of the early twentieth century. This as a way of undeniable responsibility, not only in the constitution of the characters, but concealed the contribution of female voices silenced, but nevertheless these dramatic texts of agitation, are fully present to value level; expressed in a female creative subjectivity that differs from the male voice with clarity. It assumed from the perspective of literary anthropology.